Pengaruh Motivasi dan Komitmen Organisasi terhadap Kinerja KaryawanPT Harian Rakyat Merdeka Jakarta Selatan - Septiana, Syifa; Farida , Syarifah Ida (Jurnal Sinergi Manajemen, 2024)
The purpose of this research is to determine the influence of motivation and organizational commitment on employee performance at PT Harian Rakyat Merdeka Jakarta. The method used is quantitative. The sampling technique used saturated sampling and a sample of 60 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that motivation has a significant effect on employee performance with a coefficient of determination value of 35.9%. Proven by the calculated t value > t table = (5.836 > 1.984). Organizational commitment has a significant effect on employee performance with a coefficient of determination value of 34.6%. Proven by the calculated t value > t table = (5.042 > 1.984). Motivation and Organizational Commitment simultaneously have a significant effect on employee performance with the regression equation Y = 1.881 + 0.670 x1 + 0.366 x2, a correlation value of 0.751. The coefficient of determination value is 34.6% while the remaining 65.4% is caused by other factors. Hypothesis testing obtained calculated F value > F table or (36.913 > 3.092).